Rancang Bangun Sistem Informasi Akuntansi Peminjaman Pada Koperasi Simpan Pinjam - Geo Halomoan Simanjuntak; Irmawati Carolina; Insan Nurachim, Rusma; Vivi Maria (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Cooperatives, as a business entity that is different from others, have their own challenges in dealing with free trade, both from the movement sector and internal problems of the cooperative itself. It is hoped that the existence of the Cooperative movement as an economic institution can act as a driving engine for national economic activity as well as a teacher shop for the Indonesian economy. Recording financial data in cooperatives is of course very important. As information technology develops, the use of computer applications as a medium for recording financial data has become quite relevant and useful. Manual financial recording media is very susceptible to problems such as recording errors or presenting reports that are less accurate and require more time. So we need an application that can make it easier to record finances in cooperatives. This research uses the software development method, namely Waterfall, starting from analysis, design, coding, testing and supporting stages. The results of this research are an accounting information system for processing savings and loan data at the Palomak Artha Mas Bekasi Cooperative based on a website that can be used for the company’s operational needs. The computerized system is expected to improve the quality of service in the cooperative.